Escalating the limit of median survival time and predictors of mortality among preterm neonates in Northwest Ethiopia, 2021: a 1-year prospective follow-up study. Issue 12 (5th December 2022) - Chanie, Ermias Sisay; Engedaw, Destaw; Eyayu, Tahir; Admasu, Fitalew Tadele; Amera, Eninur Dejen; Azanaw, Kefyalew Amogne; Kassaw, Amare; Feleke, Dejen Getaneh; Ayehu, Gashaw Walle; Jimma, Melkamu Senbeta; GebreEyesus, Fisha Alebel; Moges, Natnael; et al.
Abstract : Objectives: To examine the survival rate and predictors of mortality among preterm neonates in the neonatal intensive care unit at South Gondar public hospitals, 2021. Design: Prospective follow-up study. Setting: South Gondar public hospitals, Northwest, Ethiopia. Participants: We recruited 283 preterm neonates who were admitted at neonatal intensive care unit at selected hospitals from 15 February 2020 to 22 January 2021. Outcome measures: The primary outcome measure of this study was the survival rate of preterm neonates in the neonatal intensive care unit. Moreover, the study assessed the predictors for the occurrence of mortality by the Cox-proportional hazard model. Data were entered into Epi data V.4.2 and exported to Stata V.14 statistical software for analysis. The log-rank test determines the survival difference between predictor variables. Results: A total of 283 preterm neonates, 61 died during the follow-up. Born from antepartum haemorrhage mother (adjusted HR (AHR)=2.2 (95% CI 1.10 to 4.37)), being small weight for gestational age (AHR=4.6 (95% CI 2.22 to 9.53)), not having kangaroo mother care practice initiated (AHR=2.7 (95% CI 1.39 to 7.74)), hypothermia (AHR=4.0 (95% CI 1.96 to 8.30)) and perinatal asphyxia (AHR=3.9 (95% CI 1.97 to 7.94)) were significant predictors of preterm neonate mortality. Conclusion: In this study, the preterm neonates survival rate (78.4%) and the median survival time (21 days) were found to be low. Preventing and managing the predictors, including an antepartum haemorrhagic mother, small weight for gestational age, hypothermia and prenatal asphyxia, is crucial. In addition, more emphasis should be placed on initiating universal kangaroo mother care practice soon after birth to increase the survival of preterm neonates.